Metacognitive Judgments in Learning the Derivative Concept Using the Virtual Lab Strategy - Rubén Darío Lara Escobar; Oscar Cárdenas Delgado; Yeison A. Garcés Gómez; Paulo Andrés Parra; Paula Andrea López Jimenez (Universidad de Caldas, 2022)
This study examined a classroom intervention through a virtual laboratory as a didactic strategy that was based on the understanding of the derivative concept applied to the problem of the tangent line. The PretestPosttest methodology was used to test if there are significant differences in the learning of the derivative concept, compared to the traditional teaching approach. The results indicate that a statistical analysis implies three categories in relation to competencies developed by the students: solution of equations, identification of terms, and conceptual questions. There was a difference in the variances of populations for the competence of solving equations, and the experimental group showed better performance in; the other two categories showed similar performance in both groups. Thus, we consider the proposed method as an alternative form of teaching the derivative concept. The metacognitive regulation strategies implemented by the students during the didactic intervention process were also identified.